An Act of Incorporation for that Part of the Northern Liberties, Lying between the Middle of Sixth Street and the River Delaware, and between Vine Street and Cohocksink Creek, with Ordinances for the Improvement of the Same, at 51, An Ordinance for the Suppression of Nuisances . . . § 8 (1824) - (:unkn) unknown (My University, 1824)
That no person or persons shall fire, or discharge any cannon, or piece of artillery, or small arms, or prove any pistol, gun, musket barrels, or cannon, or illuminate, or cause to be illuminated, any house within the regulated parts, incorporated as aforesaid, in said township
Keywords: DISCHARGE